Case Study : Pak Ali Food Industries Sdn. Bhd / Nur Syazwina Atasha Azman - Azman, Nur Syazwina Atasha (2021)
Entrepreneurship is the activity as an entrepreneur, which can be defined as‘carrying out innovation, nance and business in an eort to transform andproduce an innovation on goods and services in the economy’. This can result in new organizations or can be part of invigorating mature organizations in response to perceived opportunities. The most obvious form of entrepreneurship is starting a new business (referred to as a startup company). However, in recent years, the term has been expanded to include forms of social and political entrepreneur carries out activities in a large firm organization it is referred to as intrepreneurship. This semester, in the subject of entrepreneurship, students are assigned to choose a company to make a case study report. In this assignment, students need to research their company background and entrepreneurial competencies. For this case study , I was choosen the company from IKS products (industry kecil sederhana) that is Pak ali food industries Sdn. Bhd as the personal entrepreneurial competencies key characteristics. Through this assignment, I got some information about this company. Apart from that, I can know a lot of efforts that have been made by pak ali in developing their business so far. The company started with little capital and only sold at home but now their company is well developed and well known in Malaysia. There are many obstacles he faced from difficult to successful as it is now. His initiative, concern high quality of his products, systematic planning and persuasion some key characteristics that make him to become a successful businessman a well-known fruit pickle producer in Penang.